Cover Feature: Extending the Library of Light‐Dependent Protochlorophyllide Oxidoreductases and their Solvent Tolerance, Stability in Light and Cofactor Flexibility (ChemCatChem 16/2020). Issue 16 (21st August 2020) - Schmermund, Luca; Bierbaumer, Sarah; Schein, Viktor K.; Winkler, Christoph K.; Kara, Selin; Kroutil, Wolfgang
Abstract : The Cover Feature brings the enzyme named 'Light‐Dependent Protochlorophyllide Oxidoreductases' (LPOR) into the light. LPORs can be found in plants and other phototrophic organisms. It catalyzes the light‐driven reduction of a C=C double bond in the molecule pchlide to chlide, which is a key intermediate in the biosynthesis of chlorophyll. In their Full Paper, L. Schmermund et al. describe the identification of LPORs that also accept NADH as cofactor, which is unique since until now only NADPH‐dependent LPORs have been described (Cover designed by Verena Resch, Luminous lab). More information can be found in the Full Paper by L. Schmermund et al.